Utilization of an intra-oral diamagnetic passive shim in functional MRI of the inferior frontal cortex. - Wilson, J; Jezzard, P (2003)
Due to the presence of gross magnetic susceptibility artifacts, functional MRI (fMRI) has proved problematic in studies of the human inferior frontal cortex (IFC). There is a strong desire, therefore, to employ techniques that mitigate susceptibility artifacts in the IFC while preserving the imaging parameters of an fMRI study. It has been shown that the use of a single, strongly diamagnetic, intra-oral passive shim significantly improves the homogeneity of the static magnetic field (B(0)) and, as a result, alleviates the susceptibility artifacts within the IFC. In this study, practical issues regarding the use of an intra-oral passive shim are examined. We investigated B(0) instabilities within the IFC resulting from subject head motion in order to calculate the effects of an intra-oral passive shim on the temporal variance of an EPI time series. These studies show that the addition of an intra-oral passive shim improves both B(0) homogeneity and signal stability, and increases sensitivity to functional activation.